(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The article's research focus is to investigate the impact of technologies used in smart cities to achieve environmental sustainability. The research methods used to review scientific studies worldwide on the problem under consideration, analysis and synthesis, comparative analysis, and logical approach. The information and communication technologies in smart cities aim to promote sustainability and provide adequate services to citizens, thereby improving their quality of life. Specific characteristics of smart cities are the extensive use of technology, real-time monitoring, innovation, and citizen empowerment, with a constant focus on sustainability. Analysis of the cited examples shows that technologies are being deployed in smart cities to improve transportation systems, deal with traffic jams and waiting times at traffic lights, and more with real-time data analysis. In most examples, information and communication technologies create a smart grid to achieve optimal energy use and improve the efficiency, reliability, and economy of the provided utility services. Self-monitoring and control of smart grids are realized using intelligent sensors and smart meters for energy transmission and distribution for real-time analysis of current consumption. An intelligent energy system involves using technologies for efficient energy production and distribution. The conducted case study on the effectiveness of the smart city in terms of environmental sustainability establishes that the sustainable management of resources and reducing the harmful impact on climate change and the environment requires optimizing the use of energy and resources and increasing the use of renewable energy sources. Analysis shows how technology can achieve environmental sustainability by reducing carbon emissions from cities, improving air quality, and optimizing the use of natural resources. Implementing intelligent systems and applications can reduce greenhouse gas emissions by an average of 20%, water consumption by up to 30%, and the amount of non-recyclable solid waste by around 15-20%, depending on the city's specific characteristics.